Oxidative stability and elemental analysis of sunflower (Helianthus annuus) edible oil produced in Brazil using a domestic extraction machine - Machate, David Johane; Melo, Elaine S. P.; Oliveira, Lincoln Carlos Silva de; Bogo, Danielle; Michels, Flávio S.; Pott, Arnildo; Cavalheiro, Leandro F.; Guimarães, Rita de Cássia Avellaneda; Freitas, Karine de Cássia; Hiane, Priscila Aiko; Caires, Anderson R. L.; Vilela, Marcelo Luiz Brandão; et al. (Frontiers in Nutrition, 2022)
Regular vegetable oils’ consumption is associated with energy acquisition, nutritional benefits, health improvement, and metabolic diseases regulation. This study evaluated fatty acids composition, physicochemical, thermal, oxidative, and optical properties, and quantified trace elements in the sunflower oil extracted by a domestic cold-press machine. The oil presented linoleic (54%) and oleic (37.29%) primary of the unsaturated fatty acids (91.67%), which atherogenic (0.05), thrombogenic (0.16) and hypocholesterolemic/hypocholesterolemic (21) indices demonstrated to be suitable for human consumption and possible health promotion. In addition, trace elements concentrations by IC OES were ordered Zn > Fe > Al > Cu > Mn > Cr. Concentrations of Zn, Fe, Al, Cu and Mn were lower than FAO/WHO and DRI/AI limits, while Cr concentrations exceeded the FAO/WHO limits, which can be used as an indicator of the polluted ambiance. Possible sunflower oil quantities daily consumption were calculated considering non-carcinogenic risk (CR < 10–4), and total non-carcinogenic hazard index (HI < 1). Based on trace elements determined in this study, the suitable quantity of sunflower oil consumption varies according to individuals aged 8, 18, and 30 years shall be deemed 0.61, 1.46, and 1.65 g/kg, respectively, attending HI = 0.99, and CR < 10–4.